The Effect of Solvency, Profitability, Growth, and Firm Size on Firm Value in Indonesia’s Oil and Gas Subsector (2019–2023) - Fadilah, Muhamad Althoriq Alwi; Susyani, Novi (International Journal of Education, Management, and Technology, 2025)
This study addresses the limited research on financial determinants of firm value in Indonesia’s oil and gas subsector, a strategic industry for both energy security and capital market performance. It examines the effects of solvency, profitability, firm growth, and firm size on firm value during 2019–2023. Using a quantitative approach, secondary data from 13 listed companies were selected through purposive sampling, sourced from audited annual reports, and analyzed using panel regression with the Random Effect Model. The findings reveal that profitability (ROA) has a significant positive effect on firm value (PBV), whereas solvency (DER), firm size (LN.TA), and firm growth have no significant effects. These results suggest that in a capital-intensive, commodity-driven sector, operational efficiency is a stronger driver of market valuation than scale or leverage. Managerially, oil and gas companies should prioritize improving ROA through cost efficiency, asset optimization, and stable production rather than focusing solely on asset expansion. For investors, profitability emerges as a more reliable valuation indicator than firm size or debt structure. For regulators and the Indonesia Stock Exchange, sector-specific disclosures emphasizing operational efficiency and production performance could enhance market transparency. Future studies are encouraged to incorporate macroeconomic variables, global oil price movements, and non-financial performance metrics to provide a more comprehensive understanding of firm value in the energy sector.